Realisasi Pemilihan Beberapa Nama Untuk Mengisi Satu Jabatan Sebagai Pimpinan Tinggi Pratama di Lingkungan Pemerintah Kota Pekanbaru Menurut Undang-Undang Nomor 5 Tahun 2014 Tentang Aparatur Sipil Negara - Nurhadi, Nurhadi; Almadison, Almadison (ALSYS, 2022)
The implementation of regional autonomy in Indonesia has resulted in a paradigm shift and a centralized monolithic government system in the Central Government towards a decentralized system of government in the Regional Government. This kind of government provides flexibility to regions in the form of broad and responsible regional autonomy, to regulate and manage the interests of local communities based on democratic principles, participation, initiatives and the aspirations of the people themselves on the basis of equity, justice and in accordance with the conditions, potential and regional diversity. Efforts to support the success of regional autonomy must be supported by state apparatus as implementers of government policies or regulations. The State Civil Apparatus (ASN) as human resources in charge of serving the public interest has a role in realizing the implementation of government duties and the implementation of national development. The implementation of national development is very dependent on the ability and perfection of the state apparatus which in essence also depends on the perfection of the ASN. Therefore, ASN should have good quality in order to be able to carry out their duties in a professional, fair, responsible, precise and correct manner.